SYNTHESIS OF SR1-XSNXTIO3 AS LEAD-FREE FERROELECTRIC MATERIAL USING SONOCHEMICAL METHOD - Nurhasanah, Siti
Ferroelectric material PbTiO3 (PT) has been used commercially in various electric devices such as capasitor, sensor, detector and memory device. However PT contains of Pb, which is known as one of hazardous element and can pollute the environment so the uses are limited. SnTiO3 (ST) has been studied with computational method to replace PT and it was shown that ST has similar properties with PT. Attempt to synthesis ST has been carried out by sonochemical method, but it have not obtained a good results. Meanwhile the study also conducted by substitution of Sn2+ in SrTiO3 to see the posibility of the formation of pure ST phases. The pure phase of Sr1-xSnxTiO3 is only obtained for x = 0.1and it has been synthesized by sonochemical method. The lattice parameters was clarified by using crystal X-ray diffraction data which are also processed by Rietica Program, Winplot and Find it. The results give lattice parameter of a = 3.9106 (4) Å, cell volume = 59.806 (3) Å3. The crystal structure are classified into simple cube and perovskite-type within Pm3m space group. Other characterizations include Scaning Electron Microscopy – Energy Dispersive Spectroscopy (SEM-EDS) and capacitance measurement using LCR meter. These compounds have an anomaly at temperature arround 425 oC on dielectric constant data. These results may suggest the posibility that Sr1-xSnxTiO3 is ferroelectric.